Microbial Contamination of Nebulizers in Patients With Cystic Fibrosis - Cansu Yilmaz Yegit; Pinar Ergenekon; Nurcan Duman; Hakan Mursaloglu; Muruvvet Cenk; Burcu Suzer Uzunoglu; Gamze Tastan; Yasemin Gokdemir; Ela Erdem Eralp; Aysegul Karahasan Yagci; Fazilet Karakoc; Bulent Karadag (Turkish Archives of Pediatrics)
Objective: Nebulizer contamination has potential harmful effects on the respiratory system. The aim was to investigate the contamination profile of the nebulizers in cystic fibrosis patients and evaluate the relationship between hygiene practices and microbial contamination.